The Procedural Subjects in the Peruvian Procedural Code of 2004 (Accusatory, Guarantee, Adversative, Efficient and Effective) - Rodriguez Hurtado, Mario Pablo (2010)
The present paper analyzes the characteristics and functions that the new Criminal Procedure Code assigns to the procedural subjects in Peru. The procedural subjects that the new Code of Criminal Procedure recognizes are mainly the following: the jurisdictional body, the Public Ministry and the accused and his sponsor lawyer. It is necessary to mention that this new code strengthens the role of the victim and the civil actor. In this sense, the first place, the author develops the powers of the court, specifically, the judges. In general, these are responsible for issuing the ruling to resolve a conflict by imparting impartial justice. Some of the organs with jurisdictional competence are the Criminal Chamber of the Supreme Court, the Criminal Chambers of the Superior Courts, the Criminal Courts, the Courts of the Preparatory Investigation and the Courts of Law. One of the contributions of the criminal procedure reform is the differentiation between the Criminal Courts and the Courts of Investigation Preparatory. Secondly, the functions of the Public Ministry are analyzed. This is mainly responsible for the prosecution of the crime. The new Criminal Procedure Code establishes that the investigation is entirely under the responsibility of the prosecutor. However, the judge in charge of the preparatory investigation, or judge of guarantees, is also a participant, since he has the functions of guardianship, guarantee and control of this stage of the process. It is worth mentioning that the conduction and control of police investigation acts are also in charge of the Public Ministry. Third, the author develops the competences of the accused and his defense lawyer. It is established that these comply, fundamentally, with the defense function. These have various rights and guarantees that must be respected, for example, in the case of the accused, he has the right to know the charges against him, be assisted by a defense lawyer, to keep quiet, among others; and in the case of the sponsor lawyer, the right to intervene from the beginning of the sponsorship, to participate in all the proceedings of the process, to interpose means of defense or to challenge, etc. Finally, the victim and the civil actor have the right to information, to be heard before decisions are taken such as suspension of the criminal process; likewise, they can challenge in cases of dismissal or acquittal, whenever they request it.